Domain structure and finite-size effects in Sr2-La FeMoO6 nanoparticles: A study by magnetic measurements - Duong, Nguyen Phuc; Nguyet, Dao Thi Thuy; Loan, To Thanh; Man, Nguyen Khac; Anh, Luong Ngoc (Current applied physics, 2023)
In this work, a model for the microstructure of Sr2-xLaxFeMoO6 nanoparticles samples (0 ≤ x ≤ 0.4) was established based on scanning electron microscopy and magnetic studies. The analysis reveals antiphase crystalline domains in the particles with the size distribution centered around mean values below ~12 nm for all the samples. Such small-size domains are responsible for the superparamagnetic properties observed for temperatures below room temperature, which are dependent on their dipole interactions. According to the fraction of Fe atoms at the antiphase boundaries calculated under the spherical domain assumption, these domains have lower degrees of atomic disorder than those estimated from the saturation magnetization values at 5 K, which are consistent with the high spin polarization values previously reported. The Curie temperature values, and the broadening of the magnetic phase transition can be satisfactorily explained based on the domain size distribution. KCI Citation Count: 0